Combination therapy with rifampicin or fosfomycin in patients with Staphylococcus aureus bloodstream infection at high risk for complications or relapse: results of a large prospective observational cohort. (1st May 2020) - Rieg, Siegbert; Ernst, Angela; Peyerl-Hoffmann, Gabriele; Joost, Insa; Camp, Johannes; Hellmich, Martin; Kern, Winfried V; Kaasch, Achim J; Seifert, Harald
Abstract: Objectives: To investigate whether Staphylococcus aureus bloodstream infection (SAB) patients at high risk for complications or relapse benefit from combination therapy with adjunctive rifampicin or fosfomycin. Methods: In this post hoc analysis, SAB patients with native valve infective endocarditis, osteoarticular infections or implanted foreign devices were included. The co-primary endpoints were all-cause 90 day mortality and death or SAB-related late complications within 180 days. To overcome treatment selection bias and account for its time dependence, inverse probability of treatment weights were calculated and included in marginal structural Cox proportional hazard models (MSCMs). Results: A total of 578 patients were included in the analysis, of which 313 (54%) received combination therapy with either rifampicin ( n = 242) or fosfomycin ( n = 58). In the multivariable MSCM, combination therapy was associated with a better outcome, that is, a lower rate of death or SAB-related late complications within 180 days (HR 0.65, 95% CI 0.46–0.92). This beneficial effect was primarily seen in patients with implanted foreign devices, in which combination therapy was associated with a lower rate of death or SAB-related late complications within 180 days (HR 0.53, 95% CI 0.35–0.79) and a lower 90 day mortality (HR 0.57, 95% CI 0.36–0.91). Upon agent-specific stratification, we found no significant differences in outcomes between combination therapy containing rifampicin and fosfomycin; however, the number of patients in most subgroups was not large enough to draw firm conclusions. Conclusions: In patients with implanted foreign devices, combination therapy was associated with a better long-term outcome. Larger prospective studies are needed to validate these findings.